1982
DOI: 10.1111/j.1432-1033.1982.tb07030.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Streptomyces aureofaciens Protein‐Synthesis Elongation Factor Tu in an Aggregated State

Abstract: The ability of EF‐Tu to aggregate spontaneously was employed for the purification of homogeneous EF‐Tu · GDP from Streptomyces aureofaciens. The formation of filamentous structures in the aggregated EF‐Tu was demonstrated in a light microscope. The purified factor, with a specific activity of 19 100 ± 1000 units/mg in [3H]GDP exchange, was shown to be active in the translation of poly(U). Aggregated EF‐Tu · GDP exhibited almost eight‐times lower GDP‐exchange capacity at 2°C than at 30°C. This suggests that GDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Sedimented pellets resuspended in a small amount of buffer A were used as a "membrane fraction". EF-Tu from S. aureofaciens was purified according to Weiser et al (1982). To prove the embedding of EF-Tu in membranes we centrifuged the membrane fraction in the SS-34 rotor through 30 % sucrose cushion (20 000 rpm, 1 h).…”
Section: Methodsmentioning
confidence: 99%
“…Sedimented pellets resuspended in a small amount of buffer A were used as a "membrane fraction". EF-Tu from S. aureofaciens was purified according to Weiser et al (1982). To prove the embedding of EF-Tu in membranes we centrifuged the membrane fraction in the SS-34 rotor through 30 % sucrose cushion (20 000 rpm, 1 h).…”
Section: Methodsmentioning
confidence: 99%
“…6), might be explained by storage of the factor for later use. We have previously shown that Streptomycetes EF-Tu can spontaneously aggregate (Weiser et al 1981(Weiser et al , 1982; this mechanism may be utilised by differentiating cells to store EF-Tu.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies we compared some of the functional and structural properties of EF-Tu from Streptomyces aureofaciens vegetative mycelium and E. co# which revealed a high degree of functional and structural similarity between the two proteins [4][5][6]. Here we have identified the EF-Tu in spores of S. aureofaciens and we describe a membrane bound protease from spores which cleaves the EF-Tu in spore cell-free homogenates.…”
Section: Introductionmentioning
confidence: 88%